Evaluation of Farmers' Bottlenecks to Innovate and Adopt New Technologies in Egypt - Salem, Shaban Ali; M. Oumer, Ali; Dhehibi, Boubaker; Abda-Allah Abdallah, Iman; Souissi, Asma; Baum, Michael (International Center for Agricultural Research in the Dry Areas, 2024)
The objective of this research was to analyze and evaluate farmers' bottlenecks and risks to innovate and adopt new technologies in Egypt. A literature review as well as key informant and focus group discussion were conducted to assess the bottlenecks to technology adoption by farmers in Egypt. Literature review results indicate that several personal, social, economic, institutional and policy-related bottlenecks hinder the adoption of innovation packages by Egyptian farmers in various production contexts. For example, the main bottlenecks that farmers face while using raised-bed technology package for mitigating salinity include insufficiency of raised-bed machines, high production costs, lack of regular maintenance for the available raised-bed machines, lack of chemical fertilizers, poor distribution of improved wheat seeds and lack of good pesticides. The results of key informant and focus group discussions show that price distortions are key bottlenecks for major crops such as maize, rice and wheat due to market inefficiency in the agriculture sector. In addition, the use of agricultural machinery, agricultural extension services and agricultural cooperatives are also key aspects that farmers face bottlenecks in their production and marketing of major agricultural commodities. It is crucial to address these bottlenecks through well-designed agricultural policies to help farmers adopt sustainable agricultural innovation practices in Egypt.